Effect of electrolytic and chemical lesion by ibotenic acid of the amygdala on salt intake - Saad, W. A. [UNESP]; Paulino, M. A. [UNESP]; Camargo, L. A.A. [UNESP]; Renzi, A. [UNESP]; Menani, J. V. [UNESP]; Abrao-Saad, W. [UNESP] (My University, 1994)
Sodium chloride intake was studied in male Holtzman rats weighing 250-300 g submitted to electrolytic and chemical lesion of the cell bodies, not fibers of the amygdaloid complex. Sodium chloride (1.5%) intake increased in animals with electrolytic lesion of the corticomedial nucleus of the amygdala. Sodium chloride (1.5%) intake increased after ibotenic acid injection into the corticomedial nucleus of the amygdala to a larger extent (26.6 ± 9.2 to 147.6 ± 34.6 ml/5 days). The results indicate that sodium intake response can be induced by lesions, which involved only cell bodies. The fibers of passage of the corticomedial nucleus of the amygdala produce a water intake less consistent than that induced by ibotenic acid, which is more acute. The results show that cell bodies of this region of the amygdala are involved in the control of sodium chloride intake.
Keywords: amygdala; electrolytic lesion; ibotenic acid lesion; sodium intake